FR1.3: Gendered Impacts of Covid-19 in 4 Countries: Kenya, Niger, Rwanda, and Uganda - Bryan, Elizabeth; Mawia, Harriet; Ringler, Claudia (International Food Policy Research Institute, 2022)
The COVID-19 pandemic had unprecedented effects on the lives and livelihoods of men and women in rural settings, where gender inequalities in access to and control over productive resources and economic opportunities persist. To identify and monitor the differential effects of the pandemic, IFPRI conducted phone surveys in Kenya, Niger, Rwanda, and Uganda. The study investigated income disruptions, food insecurity, coping strategies and policy responses by respective governments during the pandemic. A descriptive analysis of the phone survey data was conducted using Stata software, and statistical tests were carried out to show differences between men and women respondents in their experiences with the pandemic and coping responses. The findings indicate that the COVID-19 pandemic had far-reaching impacts on people living in rural areas of the study countries including losses in income, depletion of savings and assets, and reduced access to food. While both men and women were affected by the pandemic, the ways in which men and women experienced and responded to COVID-19 varied. While many respondents reported challenges with food insecurity few received any social protection. Most gender-sensitive measures and responses were geared towards combating the increased incidence of gender-based violence, while far fewer aimed to secure women's livelihoods to help them rebound from pandemic-related income losses. Given context-specific nuances in how the pathways of impact and coping responses play out differently for men and women, interventions should be designed with considering the needs of women and girls through a consultative process with relevant stakeholders.